Insurgent communities how protests create a Filipino diaspora - Quinsaat, Sharon M. (The University of Chicago Press, 2024)
"The term "diaspora" is used so commonly that its definition, a community of people living away from their ancestral homeland, seems self-evident. But how do migrants come to form a group, and how do they understand that homeland? In this book, sociologist Sharon Quinsaat sheds new light on the meaning of diaspora through the stories of Filipino migrants who, on first arrival to their new homes in the Netherlands and the US, don't necessarily connect to their Filipino identity or other Filipinos. They maintain ties to the homeland through family, often in the form of remittance payments, but they don't see themselves as part of a Filipino community abroad. After all, how much common ground could there be between a masters student at a private US university and an undocumented domestic worker earning less than minimum wage? Quinsaat shows that these gaps are bridged when Filipinos become engaged in political activism. Quinsaat analyzes three distinct protest movements--against the regime of former dictator Ferdinand Marcos, for migrants' rights abroad, and around cultural memory of the Marcos regime--that strengthened Filipino identity among migrants as they gathered collectively to make shared demands in public. These movements bring together very different migrants with a newfound shared goal, requiring them to openly address their different experiences and relationships to their homeland and its history. Social movements thus provide an essential space not just for coming together as diasporic subjects, but for openly negotiating and working through the diversity of migrants' experiences. She also shows that this local engagement with other migrants in a new country of residence quickly ties into a global network of activism. Activist groups forge connections with others living abroad, creating new diasporic identities that crisscross the globe by way of shared political commitments. Spanning five decades, Quinsaat's project helps us understand not just a major migrant group, but how people come to see themselves as part of a collective"-- Provided by publisher.